Rheological characteristics of solvent-cast poly(epsilon-caprolactone)/organoclay nanocomposite - Hong, C. H.; Lee, C. H.; Choi, J. S.; Hong, S. M.; Choi, H. J. (NANOSCIENCE AND TECHNOLOGY, PTS 1 AND 2, 2007)
As an effective way to enhance various properties of polymer, polymer/clay nanocompoiste is being adopted since it can hybrid the properties of the two components, showing superior physical and mechanical properties. In this study, poly(E-caprolactone) (PCL) nanocomposites using an organoclay were prepared by a solution intercalation method, and their unique internal structures and theological properties induced by the presence of organoclay at nano level were studied using WARD and a rotational rheometer.